Clinically oriented anatomy - Moore, Keith L.; Dalley, Arthur F.,;Agur, A. M. R. (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins Health, 2014)
Clinically Oriented Anatomy provides first-year medical students with the clinically oriented anatomical information as it relates to the practice of medicine, dentistry, and physical therapy. The 7th edition features a fully revised art program to ensure consistency and cohesiveness of imaging style--Provided by publisher.
Thorax -- Abdomen -- Pelvis and perineum -- Back -- Lower limb -- Upper limb -- Head -- Neck -- Summary of cranial nerves.
Includes bibliographical references and index.
Keywords: Anatomy